Organocatalytic Approaches Towards the Synthesis of Asymmetric Tetrahydroquinoline (THQ) Derivatives - Kant, Kamal; Naik, Priyadarshini; Patel, Chandresh Kumar; Some, Sanjukta; Banerjee, Sourav; Aljaar, Nayyef; Atta, Ananta K.; Malakar, Chandi C. (Synthesis, 2024)
1,2,3,4-Tetrahydroquinolines (THQs) are present in molecules with significant biological importance and pharmaceuticals with diverse biological activities. Various synthetic routes have been developed to tetrahydroquinolines, such as the hydrogenation of quinolines, domino reactions, intramolecular cyclization, and notably, the Povarov reaction. Organocatalysts are small, chiral organic molecules that can successfully catalyze organic transformations. This review examines the use of organocatalysts in the asymmetric synthesis of tetrahydroquinoline derivatives using aminocatalysis, NHC catalysis, and H-bonding catalysis covering the literature between 2000 and early 2024.1 Introduction2 Aminocatalysis3 NHC Catalysis4 H-Bonding Catalysis5 Miscellaneous6 Conclusion
Keywords: organocatalysis; tetrahydroquinolines; aminocatalysis; NHC catalysis; H-bonding catalysis; Povarov reaction